Endoplasmic Reticulum Stress and Intestinal Inflammation: A Perilous Union - Eugene, Sanchez Preethi; Reddy, Vadde Sudhakar; Trinath, Jamma (Frontiers in Immunology, 2020)
The intestinal tract encompasses the largest mucosal surface fortified with a fine layer of intestinal epithelial cells along with a highly sophisticated network of the lamina propria immune cells that are indispensable to sustain gut homeostasis. However, it can be challenging to uphold homeostasis when these cells in the intestine are perpetually exposed to insults of both endogenous and exogenous origin. The complex networking and dynamic microenvironment in the intestine demand highly functional cells ultimately burdening the endoplasmic reticulum (ER) leading to ER stress. Unresolved ER stress is one of the primary contributors to the pathogenesis of inflammatory bowel diseases (IBD). Studies also suggest that ER stress can be the primary cause of inflammation and/or the consequence of inflammation. Therefore, understanding the patterns of expression of ER stress regulators and deciphering the intricate interplay between ER stress and inflammatory pathways in intestinal epithelial cells in association with lamina propria immune cells contribute towards the development of novel therapies to tackle IBD. This review provides imperative insights into the molecular markers involved in the pathogenesis of IBD by potentiating ER stress and inflammation and briefly describes the potential pharmacological intervention strategies to mitigate ER stress and IBD. In addition, genetic mutations in the biomarkers contributing to abnormalities in the ER stress signalling pathways further emphasizes the relevance of biomarkers in potential treatment for IBD.